2023
DOI: 10.3389/fcomm.2023.1063345
|View full text |Cite
|
Sign up to set email alerts
|

The “wall of text” visual structure of academic conference posters

Abstract: Posters created for conferences are a type of visual communication that are used frequently by academics. There are rarely any formatting requirements beyond fitting on their provided boards. Because posters are usually created by researchers rather than experienced graphic designers, the visual structure of conference posters may be influenced by the common format for journal articles, where text is given primacy over graphics and structured as “introduction, methods, results, discussion.” To test this, I exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Visual Impression Rubric: Following from modern validity theory, 8 evidence for both content and reliability would provide initial validity evidence for scores from a newly-created visual impression rubric. From a content evidence standpoint, most experts in prior literature highlighted that posters are a visual medium, 1 , 3 , 9 , 10 , 11 , 12 , 13 , 14 , 15 and empirical research corroborated this. 4 , 16 , 17 , 18 , 19 Within this reviewed literature, investigators uncovered themes of using graphics , limiting text , and logically organizing the poster layout.…”
Section: Methodsmentioning
confidence: 99%
“…Visual Impression Rubric: Following from modern validity theory, 8 evidence for both content and reliability would provide initial validity evidence for scores from a newly-created visual impression rubric. From a content evidence standpoint, most experts in prior literature highlighted that posters are a visual medium, 1 , 3 , 9 , 10 , 11 , 12 , 13 , 14 , 15 and empirical research corroborated this. 4 , 16 , 17 , 18 , 19 Within this reviewed literature, investigators uncovered themes of using graphics , limiting text , and logically organizing the poster layout.…”
Section: Methodsmentioning
confidence: 99%
“…Guides and resources are published to help life scientists create powerful posters. Posters, however, pose a challenging visualization format to create and are oftentimes not attractive to audiences (Faulkes, 2023). In this perspective we surveyed those preparing posters about their current challenges and approaches when designing scientific posters.…”
Section: Discussionmentioning
confidence: 99%
“…A commentary recounts all that can go wrong with poster presentations, such as too much text, cryptic abbreviations, inconsistent colours, and a lack of visual order (Wolcott, 1997). A recent study quantified this: the authors reveal that the format of award-winning posters at life science conferences still adheres to the standard format, with the majority, 75%, of posters using the "Introduction, methods, results, discussion" format and are heavy on text, colloquially referred to as the "wall of text" (Faulkes, 2023). The author also demonstrated that at least 30% of these pre-selected, award winning posters had no clear reading orientation, and overall less than 50% of the posters followed good graphic design practices (Faulkes, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations